PENGARUH SOCIAL INFLUENCES TERHADAP STICKINESS PEMBELIAN POWERAMP PREMIUM - Kevin, Kevin; Wella, Wella (ULTIMA Management, 2023)
Abstract- Poweramp is an application that is divided into 2, freemium and premium, Poweramp application is a music player application that is ranked as number 1 in Google Play. Poweramp application can be downloaded through Google Play. Poweramp freemium have been downloaded by 45 million people, meanwhile Poweramp premium have been downloaded by 1 million people. There are significant differences between Poweramp freemium and premium application. This phenomenon is used as a basis for comparisons between free and paid applications that are increasingly appearing. Many free applications that actually deliver viruses and malware. Therefore, this research aims to analyze the factors that influence a person to download Poweramp freemium application and buying the Poweramp premium. In the process of doing this research, literature reviews from other relevant journals are needed. Amidst the research, a questionnaire is created with Google Form and is distributed to respondents that have already buy Poweramp premium application. There are in total 100 valid responses that is gathered from the respondents. The data that have been gathered are then analyzed with Partial Least Square method by using SmartPLS software. The stages that is needed to be done in PLS method are to rate the Measurement Model, Discriminant Validity, Reliability Test, Average Variance Extracted (AVE), and to analyze the hypothesis received from the output of Result for Inner Weights. Results from the research shows that social factors have significant influence towards people's decision to download Poweramp freemium application, and continuing to buy Poweramp premium application. Keywords: Application; Poweramp; Social Factors; Stickiness; Partial Least Square